2018
DOI: 10.1049/iet-nbt.2017.0097
|View full text |Cite
|
Sign up to set email alerts
|

Screening the UV‐blocking and antimicrobial properties of herbal nanoparticles prepared from Aloe vera leaves for textile applications

Abstract: Nanomaterials play a vital role in textile industries due to their unique properties and applications. There is an increase in the use of nanoscale phyto products in textiles to control the bacterial infection in fabrics. Here, natural herbal nanoparticles of different sizes were prepared from shade-dried plant leaves using ball milling technique without any additives. The amorphous herbal nanoparticles possess an average particle size of 40 ± 2 nm and UV-absorption maximum at 269 nm. nanopowders-chitosan nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 31 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Durability of UPF value for the herbal nanoparticle extracted from Aloe vera, treated cotton fabric has been studied by Subramani et al Nanoparticles were applied on the textiles surface by coating with chitosan. UPF of washed fabric has been slightly decreased (7-10%) for fifth and tenth washing cycles due to the removal of coating materials [96]. In an another study, Subramani et al reported similar result for the UPF after washing, when the fabric has been treated with nanoparticle extracted from natural extract such as Azadirachta indica (neem) [97].…”
Section: Durability Of Uv Blocking Properties For Nanoparticle Treate...mentioning
confidence: 80%
“…Durability of UPF value for the herbal nanoparticle extracted from Aloe vera, treated cotton fabric has been studied by Subramani et al Nanoparticles were applied on the textiles surface by coating with chitosan. UPF of washed fabric has been slightly decreased (7-10%) for fifth and tenth washing cycles due to the removal of coating materials [96]. In an another study, Subramani et al reported similar result for the UPF after washing, when the fabric has been treated with nanoparticle extracted from natural extract such as Azadirachta indica (neem) [97].…”
Section: Durability Of Uv Blocking Properties For Nanoparticle Treate...mentioning
confidence: 80%
“…Moreover, the remarkable improvement in both the coloration and functionalisation properties (UV‐protection function and antibacterial efficacy of the fabricated samples), could be discussed in terms of the positive impact of the used bioactive materials on: (a) enhancing the extent of binder film formation, pigment colourant fixation, and other ingredients onto the fabric surface during the thermofixation (darker depth of shade), (b) upgrading the UV‐protection capability of a simultaneously coloured and functionalised fabric surface by increasing the extent of absorption, reflection, scattering and/or blocking the harmful UV‐radiation, because of the presence of active phytochemical constituents, 40 and (c) increasing the antibacterial efficacy of the treated substrates by inhibiting the growth of pathogenic bacteria because of bioactive constituents and antibacterial effects, 41‐43 keeping other parameters fixed.…”
Section: Resultsmentioning
confidence: 99%
“…However, chemical reactions are usually accompanied with the conformational change, which could release detrimental chemicals and ROS, leading to the harm to the human skin. Besides, the UPF for organic UV shields is usually below 100, which is inferior to the inorganic ones 88 , 89 .…”
Section: Functional Materials and Structural Design For Improved Ppe Performancementioning
confidence: 99%